PENGARUH MEKANISME CG DAN UKURAN KAP TERHADAP AUDIT DELAY DENGAN JUMLAH ANAK PERUSAHAAN SEBAGAI VARIABEL MODERASI - Yulistin Ferdianto; Sukrisno Agoes; Michele Kristian (Jurnal Kontemporer Akuntansi, 2022)
The corporate governance should ensure management maximizes shareholder value, by providing relevant information which reflected in the Financial Statement. This study aims to verify the correlation between corporate governance mechanisms, reflected by audit committee, board of commissioners and independent commissioners, in addition audit firm size to audit delay, and the subsidiaries as a moderating variable. This study uses a population of holding companies that publish their financial statements on the Indonesian Stock Exchange in 2012-2019. The samples are selected with a purposive sampling method. There are 414 holding companies selected as the samples for the period of 2012-2019. The analysis method used in this study are multiple regression and MRA. The results of this study indicate that the audit committee size and the board of commissioner size have a negative effect on audit delay, but the independent commissioners and audit firm size have an insignificant effect on audit delay. Moreover, subsidiaries are proven to weakens the influence of audit committee size to audit delay and subsidiaries are proven to strengthen the influence of the board of commissioner size to audit delay. While subsidiaries do not moderate the influence of the independent commissioners and audit firm size to audit delay.